Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1007/s40121-020-00372-9
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Probiotics Supplementation on Gut Microbiota After Helicobacter pylori Eradication: A Multicenter Randomized Controlled Trial

Abstract: Introduction Helicobacter pylori eradication therapy may lead to the perturbation of gut microbiota. We aim to investigate the impact of probiotics on eradication rate and gut microbiota during eradication therapy. Methods A total of 162 patients receiving bismuth quadruple therapy were enrolled and randomly assigned to groups given probiotics ( n = 83) or placebo ( n = 79) for 4 weeks. Fecal samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 35 publications
3
50
0
Order By: Relevance
“…Quadruple therapy with bismuth during 10 or 14 days also led to decreased bacterial diversity but not all the studies found a total recovery of bacterial diversity evaluated from 6 weeks to 1 year posttreatment (16,36,38,44). By contrast, concomitant therapy of three antibiotics (amoxicillin, clarithromycin, metronidazole) without bismuth for 14 days decreased bacterial diversity, but it was fully (35) or partly restored (36) at 2 months or 1 year posttreatment, respectively.…”
Section: Modulation Of the Gut Microbiota By Antibiotic-based H Pylori Eradication Therapiesmentioning
confidence: 94%
See 4 more Smart Citations
“…Quadruple therapy with bismuth during 10 or 14 days also led to decreased bacterial diversity but not all the studies found a total recovery of bacterial diversity evaluated from 6 weeks to 1 year posttreatment (16,36,38,44). By contrast, concomitant therapy of three antibiotics (amoxicillin, clarithromycin, metronidazole) without bismuth for 14 days decreased bacterial diversity, but it was fully (35) or partly restored (36) at 2 months or 1 year posttreatment, respectively.…”
Section: Modulation Of the Gut Microbiota By Antibiotic-based H Pylori Eradication Therapiesmentioning
confidence: 94%
“…There is growing evidence that antibiotic-based therapies for H. pylori eradication promote alterations in the gut microbiota (10,11,16,17,24,(35)(36)(37)(38)(39)(40)(41)(42)(43)(44), but different antibiotic combinations can exert differential effects on microbial community (166) (Table 2). In addition, proton pump inhibitors (PPI) which is usually administered together antibiotics for H. pylori eradication also contributes to bacterial shifts in the intestine (167).…”
Section: Modulation Of the Gut Microbiota By Antibiotic-based H Pylori Eradication Therapiesmentioning
confidence: 99%
See 3 more Smart Citations